Child Marriage in Nepal: Stakeholders’ Perspective - Gautam, Kamal (Journal of Health Promotion, 2019)
This study is about child marriage in Nepal from stakeholder’s perspective. It includes school going girls, women, teachers, health post staffs and local politicians as stakeholders and intends to find the situation, effects and perfectives of stakeholders on child marriage in Nepalese context. It comprises both qualitative and quantitative aspects followed by interview schedule and FGDs as tools. Fathers, relatives and friends were responsible for the incidence of early marriage in study site. Regarding effects, problems to become self dependent and deprivation of opportunity are the major effects that respondents had to face in their life. Workload in the families seems another effect to be faced followed by health problems to be experienced. Bleeding during pregnancy, low count of RBC, weakness, postpartum complications were seen in mothers during and after child births. Teenage mothers being more likely to experience complications during pregnancy and less likely to be emotionally, physically and psychologically prepared to deal with pregnancy related challenges, which often leads to maternal illness and consequently death was seen as the main conclusion of this study.